Influence of pilates method on the treatment of nonspecific chronic low back pain: a protocol study for a randomized, controlled, blind trial - Souza, Bianca Martins de; Silva, Daiane Oliveira da; Justo, Lais Paraguai; Lazzareschi, Leandro; Biasotto-Gonzalez, Daniela Aparecida; Santos Glória, Igor Phillip dos (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Low back pain is one of the most common musculoskeletal problems among workers. Studies estimate that 90% of the adults will suffer at least one episode of low back pain in life that will lead to the temporary interruption of work. A type of exercise that has gained increasing popularity among individuals with low back pain in the last decade is the Pilates method. Objective: Determine the influence of the Pilates method on improvements in pain, kinesiophobia, central sensitization and function in patients with chronic nonspecific low back pain. Methods: Thirty-four male and female volunteers between 18 and 35 years of age with a complaint of nonspecific low back pain for at least three months will be divided into two groups: Pilates method and control group. An evaluation chart created by the authors will be used to collect data on personal information, history of diseases, alcohol use, smoking, pain intensity (visual analog scale) and medications used. The Tampa Scale for Kinesiophobia, Central Sensitization Questionnaire and Oswestry Disability Index will also be administered. Pilates exercises will be performed three time per week for four weeks and administered by a researcher with adequate training in the method. Reevaluations will be performed after the sixth treatment session in the Pilates group, two weeks after the initial evaluation in the control group, after the 12th session in the Pilates group and after four weeks in the control group. Another reevaluation will be performed three months after treatment. Results: The data will be submitted to statistical analysis and the level of significance will be set to 5%. Conclusion: Based on the results analyzed it will be possible to determine the influence of Pilates Method on improvements in pain, kinesiophobia, central sensitization and function in patients with chronic nonspecific low back pain.